Design of a hybrid wind -solar generator using a vertical axis wind turbine structure with rotating photovoltaic cells - Alajmi, Mohammad Sh Gh M M (2022)
Standalone hybrid wind-solar energy generating systems have been around for more than two decades where the early versions consist of a traditional type stand-alone wind turbine generator and several stand-alone PV-panels. Since the early 2000s, two patents have been found for a new type of hybrid wind-solar energy generator where the PV-cells are mounted onto the blades of a wind turbine generator. This allowed for a compact hybrid wind-solar generator to be realized. Very recently, two new prototypes of such a device have been proposed. The first prototype was simulated for PV-cell efficiency and temperature while the second proposed prototype focused on the simulation of rotational speed when magnets are used to levitate the turbine for less friction during rotation. Although these are important perimeters to be studied, there were no mention of the solar output current loss when the PV integrated blades rotate. Near 100% Solar energy extraction from the rotating PV-blades is a special feature/function for this type of hybrid wind-solar generator and needs to be quantified. Therefore, this thesis focuses to measure this loss by design and prototyping of a hybrid wind-solar generator with rotating PV-cells integrated into the blades of the turbine. Laboratory measurements show that approximately 4.3 % Solar generated current loss is experienced by the prototype when the turbine rotates in wind speeds ranging from 4 to 20 m/s. Since the current loss is less than 5 %, it is concluded that the functionality of the Solar-VAWT prototype is acceptable. The start-up wind speed of the VAWT was measured to be 4 m/s. On-site measurement results were also conducted and shows that the Solar efficiency, η is 2.7 % and the power coefficient, Cρ is 0.32 when measured at Location A (3.00,0.1.072). The daily average generated Solar energy is 1 Wh/day and the daily average wind energy is 0.07 Wh/day.